2020
DOI: 10.1590/1517-869220202603116858
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Values of Spanish Beach Volleyball Players in Relation to Sports Performance Level

Abstract: Introduction Since its debut at the 1996 Atlanta Olympics, beach volleyball has grown on the international sports scene. An extensive collection of data from several countries and levels of competition will provide a database that can be used to characterize beach volleyball players and define references for training stages. Objective The purpose of this study was to describe and compare the anthropometric profiles of Spanish male and female beach volleyball players at different levels of competition in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is also widely used to describe the body in terms of conceptual models that represent body components such as total mass, lean mass, and total fat mass (Ward, 2018). Regarding body composition and performance, the relationship between anthropometric characteristics and performance levels of beach volleyball players was examined, and as a result, it was found that athletes with high performance levels had lower body fat percentages (Escudero, Martín, Montesdeoca, Ruiz, and Manso, 2020). In another study, the effects of changes in the body composition of elite female athletes on performance were examined, and it was observed that there was a positive relationship between changes in performance and fatfree mass percentage (Tsukahara Torii, Yamasawa, Iwamoto, Otsuka, & Goto, 2020).…”
Section: Extended English Summarymentioning
confidence: 99%
“…It is also widely used to describe the body in terms of conceptual models that represent body components such as total mass, lean mass, and total fat mass (Ward, 2018). Regarding body composition and performance, the relationship between anthropometric characteristics and performance levels of beach volleyball players was examined, and as a result, it was found that athletes with high performance levels had lower body fat percentages (Escudero, Martín, Montesdeoca, Ruiz, and Manso, 2020). In another study, the effects of changes in the body composition of elite female athletes on performance were examined, and it was observed that there was a positive relationship between changes in performance and fatfree mass percentage (Tsukahara Torii, Yamasawa, Iwamoto, Otsuka, & Goto, 2020).…”
Section: Extended English Summarymentioning
confidence: 99%
“…Dyreson [1] believes that modern beach volleyball should be viewed as a global phenomenon with transnational origins. Another study [2] reported an increase in the popularity of beach volleyball since its inclusion in the Olympic Games. The authors propose creating a database that can be used to identify trends for training stages.…”
mentioning
confidence: 99%